Microstructure and oxidation properties of a neutron-irradiated Cu-13.5wt% Al-4wt% Ni shape memory alloy - Zengin, R (Elsevier, 2005)
The reverse and forward transformation temperatures, oxidation behaviour and microstructure of a neutron irradiated Cu-13.5 wt% Al-4 wt% Ni shape memory alloy have been investigated. The alloy was irradiated for 3.6 and 7.2 ks with thermal neutron flux. Neutron flux is 8 X 10(12) n cm(-2) s(-1), E > 1 McV. It was seen from differential scanning calorimetry (DSC) that transformation temperatures of the martensite double left right arrow austenite decreased and transformation enthalpies increased after neutron irradiation. The oxidation behaviour was also determined using thermogravimetric analysis (TGA). Neutron irradiation increased the mass gain rates of the alloy. The martensite morphology disappeared after neutron irradiation. As a result, irradiation leads to observable changes in the structure of the alloy. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: neutron irradiation; shape memory alloy; transformation temperatures; oxidation behaviours microstructure